Preliminary assessment of resistance among U.S. wheat cultivars to the Triticum pathotype of Magnaporthe oryzae - Cruz, Christian D.; Bockus, William W.; Stack, James P.; Tang, Xiaoyan; Valent, Barbara; Pedley, Kerry F.; Peterson, Gary L. (My University, 2012)
Magnaporthe oryzae is the causal agent of blast disease on several graminaceous plants. The M. oryzae population causing wheat blast has not been officially reported outside South America. Wheat production in the United States is at risk to this pathogen if it is introduced and established. Proactive testing of U.S. wheat cultivars for their reaction to blast and identification of resistance resources is crucial due to the national and global importance of the U.S. wheat industry. In this preliminary study, the phenotypic reaction of 85 U.S. wheat cultivars to M. oryzae (Triticum pathotype) was determined. Although there was a significant correlation in the reaction to blast at the seedling and adult plant stages, only 57% of the head reaction was explained by the seedling reaction. Because of the importance of disease development at the head stage in the field, assessment of all 85 cultivars occurred at the head stage. Among cultivars tested, a continuum in severity to head blast was observed; cultivars Everest and Karl 92 were highly susceptible with more than 90% disease severity, while cultivars Postrock, JackPot, Overley, Jagalene, Jagger, and Santa Fe showed less than 3% infection. No evidence of the presence of physiological races among isolates T-7, T-12, T-22, and T-25 was found.
Citation: Cruz, C., . . . & Peterson, G. (2009). Preliminary Assessment of Resistance Among U.S. Wheat Cultivars to the Triticum Pathotype of Magnaporthe oryzae. Plant Disease, 96, 1501-1505. https://doi.org/10.1094/PDIS-11-11-0944-RE
Keywords: Triticum pathotype; Magnaporthe oryzae; Wheat cultivars; Wheat blast